Improvement of Student Learning Outcomes through Use Google Classroom Media in Class VIII-4 Students MTsN 1 Kota Subulussalam - Candra Sihotang; Abdul Hasan Saragih; Abdul Hamid K (BIRCU, 2020)
The purpose of this study is to improve student learning outcomes in Indonesian language lessons using google classroom media. The subjects of the study were students of class VIII-4 MTsN 1 Subulussalam City, totaling 32 people consisting of 14 men and 18 women. This research uses a case study qualitative research method. Data collection techniques using observation, tests, and documentation. Then contextual data is analyzed through procedures namely: data reduction, data presentation, and drawing conclusions. The results showed an increase in student learning outcomes in learning Indonesian. This can be seen from the increase in the percentage of student learning outcomes from before the action, cycle I, to cycle II. Before the action the number of students who reached the KKM was 56.25% or 18 people. In the first cycle there was an increase to 71.88% or 23 people. Then in the second cycle there was an increase to 87.50% or 28 students. It can be concluded that the use of the google classroom application can improve learning outcomes in Indonesian subjects in class VIII-4 MTSN 1 Subulussalam City in 2019/2020.